F2R-CWANA - Approach to Science for Impact - Baum, Michael; Al-Zu'bi, Maha (2023)
Presentation on CGIAR Initiative on Fragility to Resilience in Central and West Asia and North Africa (F2R-CWANA) approach to science for impact, for the Resilient AgriFood Systems (RAFS) Regional Integrated Initiatives (RIIs) Retreat, 1 March 2023, Nairobi.